The Effect of Corporate Governance on Firm Value in Non- Financial Companies Listed on the Indonesia Stock Exchange for the 2017-2019 Period - Ramadhan, Iqbal Ryan; Pangestuti, Irene Rini Demi; Wisesa, Baskara Bayu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the effect of the implementation of corporate governance on the firm value of non-financial companies listed on the Indonesia Stock Exchange (IDX) during 2017-2019. The research data was obtained from the company's annual reports through the Indonesia Stock Exchange website, and the Diponegoro University Bloomberg Laboratory for the period 2017 to 2019. The final sample used in the study came from 85 companies with 126 data observations. The research sample was analyzed using multiple linear regression with SPSS version 25 and the method used was Ordinary Least Square (OLS). The results show that board size, board meetings, institutional ownership have a positive effect on firm value, audit committee meetings and managerial ownership have a negative effect on firm value, while public ownership and ownership concentration have no effect to value of a company.